0.55x+.05(2-x)=.10(-9)

Simple and best practice solution for 0.55x+.05(2-x)=.10(-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.55x+.05(2-x)=.10(-9) equation:


Simplifying
0.55x + 0.05(2 + -1x) = 0.10(-9)
0.55x + (2 * 0.05 + -1x * 0.05) = 0.10(-9)
0.55x + (0.1 + -0.05x) = 0.10(-9)

Reorder the terms:
0.1 + 0.55x + -0.05x = 0.10(-9)

Combine like terms: 0.55x + -0.05x = 0.5x
0.1 + 0.5x = 0.10(-9)

Multiply 0.10 * -9
0.1 + 0.5x = -0.9

Solving
0.1 + 0.5x = -0.9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.1' to each side of the equation.
0.1 + -0.1 + 0.5x = -0.9 + -0.1

Combine like terms: 0.1 + -0.1 = 0.0
0.0 + 0.5x = -0.9 + -0.1
0.5x = -0.9 + -0.1

Combine like terms: -0.9 + -0.1 = -1
0.5x = -1

Divide each side by '0.5'.
x = -2

Simplifying
x = -2

See similar equations:

| X=35+0.5x | | 4k^2-17k+4=0 | | [2b-5]+1ifb=1 | | 9(4x-7)=90x | | x=2xy | | rx^2+2r^2=3 | | 10v=-8v | | 2x^2-42x+42= | | -4c-10=2(2c-5) | | (x-2y+z)(x+2y+z)= | | rx^2+2x^2=3 | | 21+28n=42+21n | | 3x*3=x+7 | | 3x+5+4=21 | | 12h-4x=15 | | 21+28=42+21 | | 5x+3=-28 | | -4n+11=-3n-4 | | 12(2x-5)=120x | | m+23=3 | | 3y-6=2y+9 | | 5n=12 | | 5(2x-3)=40x | | 6x=8+32 | | t=2s+3.49 | | 6(x+8)=32 | | 7a+4=a | | k(n)=3n^2 | | 3(2b-1)+2b=6+9b | | (x+y-2)*(x+y-3)=0 | | -41=-23 | | (8+v)-48v=8 |

Equations solver categories